10 Years of belimumab experience: What have we learnt?. (October 2021) - Levy, Roger A; Gonzalez-Rivera, Tania; Khamashta, Munther; Fox, Norma Lynn; Jones-Leone, Angela; Rubin, Bernie; Burriss, Susan W; Gairy, Kerry; Maurik, Andre van; Roth, David A
Systemic lupus erythematosus (SLE) is a chronic autoimmune inflammatory disease affecting both adults and children. Belimumab is the only biologic approved for SLE, and the first in a class of drugs known as B-lymphocyte stimulator-specific inhibitors. The introduction of intravenous belimumab in 2011 was a major advance, being the first new therapy approved for SLE in over 50 years. As of April 2021, more than 7200 people with SLE have received belimumab in clinical studies, and it is approved in over 75 countries for the treatment of adults with SLE. A subcutaneous, self-injectable belimumab formulation was licensed in 2017 by both the US Food and Drug Administration (FDA) and European Medicines Agency (EMA). Belimumab was then approved for use in children in Europe, the USA and Japan in 2019, and China and Brazil in 2020. Recently, belimumab became the first FDA-approved drug for the treatment of adults with active lupus nephritis (LN), the most-common severe manifestation of SLE. Over the past 10 years, belimumab has established its position as a disease modifier in the SLE treatment paradigms. Robust evidence from randomised clinical studies and observational, real-world studies has demonstrated the tolerability and efficacy of belimumab for reducing disease activity and the risk of new, severe SLE flares. This enables patients to taper their glucocorticoid use, which limits damage accumulation. Significantly more patients with active LN met the criteria for renal responses and were at less risk of a renal-related event or death after receiving belimumab plus standard therapy, compared with standard therapy on top of mandatory steroid reduction. Ongoing clinical studies are evaluating belimumab's effectiveness in various indications beyond SLE. Post-marketing and registry studies are gathering additional data on key areas such as pregnancy outcomes after belimumab exposure and belimumab co-administration with other biologics.